The Role of Succinic Acid Metabolism in Ovarian Cancer - Xia, Lei; Zhang, Hairong; Wang, Xuezhen; Zhang, Xiaoyu; Nie, Ke (Frontiers in Oncology, 2021)
Ovarian cancer is one of the most common malignancies and the highest mortality among gynecological malignancy. The standard therapy options for patients with ovarian cancer are cytoreductive surgery and chemotherapy, and although most patients do better with standard treatment, it is easy to relapse and be resistant to chemotherapy. Therefore, it is important to find new therapeutic strategies. More recently, metabolic reprogramming has been recognized as a hallmark of cancer and has become a potential target for tumor therapy. Mutations of metabolic enzymes are closely related to the development of ovarian cancer. The metabolic reprogramming of ovarian cancer not only provides energy to tumor cells, but also participates in various biological processes as signaling molecules. Succinic acid (SA) is an important metabolic intermediate involved in a number of metabolic pathways, such as TCA cycle and glutamine metabolism, and is also widely present in a variety of plants and vegetables. Studies show abnormal SA metabolism in many tumors and affect tumor formation through a variety of mechanisms. But the role of SA in ovarian cancer is less studied. This paper reviews the role of SA and its abnormal metabolic pathway in ovarian cancer.